2016
DOI: 10.1007/s00125-015-3848-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat feeding leads to alterations of brain glucose metabolism in the offspring: positron emission tomography study in a porcine model

Abstract: Aims/hypothesis Maternal obesity negatively affects fetal development. Abnormalities in brain glucose metabolism are predictive of metabolic-cognitive disorders. Methods We studied the offspring (aged 0, 1, 6, 12 months) of minipigs fed a normal vs high-fat diet (HFD), by positron emission tomography (PET) to measure brain glucose metabolism, and ex vivo assessments of brain insulin receptors (IRβ) and GLUT4. Results At birth, brain glucose metabolism and IRβ were twice as high in the offspring of HFD-fed than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
(48 reference statements)
2
19
0
Order By: Relevance
“…In our model, brain response to INI in the offspring of HFDm was significantly greater at weaning and blunted (statistical significance reached only in 4 brain regions out of 11 examined) in adult age compared to controls. This is consistent with our previously published data showing that during peripheral insulin infusion in a hyperinsulinaemic-isoglycaemic clamp, brain glucose uptake in minipigs of HFD mothers was elevated in early life, and defective during young adulthood, being paralleled by cortical and hypothalamic expression of insulin receptors and insulin-sensitive glucose transporters 57 . The study suggested that the brain of animals born to obese sows was initially hypersensitive to insulin, and then became insulin resistant 57 .…”
Section: Discussionsupporting
confidence: 93%
“…In our model, brain response to INI in the offspring of HFDm was significantly greater at weaning and blunted (statistical significance reached only in 4 brain regions out of 11 examined) in adult age compared to controls. This is consistent with our previously published data showing that during peripheral insulin infusion in a hyperinsulinaemic-isoglycaemic clamp, brain glucose uptake in minipigs of HFD mothers was elevated in early life, and defective during young adulthood, being paralleled by cortical and hypothalamic expression of insulin receptors and insulin-sensitive glucose transporters 57 . The study suggested that the brain of animals born to obese sows was initially hypersensitive to insulin, and then became insulin resistant 57 .…”
Section: Discussionsupporting
confidence: 93%
“…Maternal intake of a Western-style diet during pregnancy/lactation led to changes in microbiota profile, blood lipids, cognitive responses, and hippocampal neurogenesis in swine offspring ( 45 ). Recent work by Sanguinetti et al has also shown that maternal HF feeding results in marked alterations in brain glucose metabolism in offspring thus predisposing to metabolic-neurodegenerative diseases ( 46 48 ).…”
Section: Experimental Models Of Maternal Obesitymentioning
confidence: 99%
“…A recent study showed that maternal HFD resulted in an increase in the brain insulin receptors (IRβs) in offspring at birth followed by a long-term decrease in brain glucose uptake and expression of glucose transporter 4 and IRβ in minipigs, which may increase the offspring predisposition to metabolic-neurodegenerative diseases. [ 43 ] Our team also established the mouse model of maternal HFD during pregnancy and lactation and investigated the intergenerational effects of maternal overnutrition on offspring. Similarly, our results also verified that perinatal overnutrition (HFD) changed health and disease trajectory in offspring and significantly increased the risks of glucose and lipid metabolic disorders.…”
Section: Over-nutrition In Early Life and Energy Metabolism In Later mentioning
confidence: 99%